2012
DOI: 10.1128/jb.00962-12
|View full text |Cite
|
Sign up to set email alerts
|

Polynucleotide Phosphorylase Plays an Important Role in the Generation of Spontaneous Mutations in Escherichia coli

Abstract: Polynucleotide phosphorylase (PNP) plays a central role in RNA degradation, generating a pool of ribonucleoside diphosphates (rNDPs) that can be converted to deoxyribonucleoside diphosphates (dNDPs) by ribonucleotide reductase. We report here that spontaneous mutations resulting from replication errors, which are normally repaired by the mismatch repair (MMR) system, are sharply reduced in a PNP-deficient Escherichia coli strain. This is true for base substitution mutations that occur in the rpoB gene leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…Table 2 gives mutation rates for the wild-type strain estimated using classical fluctuation tests, scoring for resistance to rifampicin (Rif R ) and to nalidixic acid (Nal R ). When normalized to the number of nucleotides that, when mutated, give the resistance phenotypes (22)(23)(24), the two mutation rates are 0.33 and 0.21 × 10 −10 mutations per nucleotide per generation, respectively. The mean rate for BPS mutations from the MA experiment was 1.99 × 10 −10 per nucleotide per generation, six-to nine-fold higher than that obtained from fluctuation tests.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 gives mutation rates for the wild-type strain estimated using classical fluctuation tests, scoring for resistance to rifampicin (Rif R ) and to nalidixic acid (Nal R ). When normalized to the number of nucleotides that, when mutated, give the resistance phenotypes (22)(23)(24), the two mutation rates are 0.33 and 0.21 × 10 −10 mutations per nucleotide per generation, respectively. The mean rate for BPS mutations from the MA experiment was 1.99 × 10 −10 per nucleotide per generation, six-to nine-fold higher than that obtained from fluctuation tests.…”
Section: Resultsmentioning
confidence: 99%
“…Long-standing work in both microbial and mammalian cells has shown that alterations of the dNTP pools can affect mutation rates (31,41,42,44,(50)(51)(52)(53)(54). More recently, studies in E. coli have shown that perturbations in the absolute levels of all four dNTPs, even when the ratios are not altered, leads to changes in mutation rates (26,55,56). Increases in the levels raise mutation rates (55,56), and decreases in the levels lead to lower mutation rates (26).…”
Section: Discussionmentioning
confidence: 99%
“…5AZ and ZEB have been used in combination in chemotherapy (20). 2-Aminopurine results principally in G·C¡A·T and A·T¡G·C changes (e.g., see references 18 and 21 to 25), as does 5BrdU (24)(25)(26). 2AP has been used to enhance the oncolytic activity of E1b-deleted adenovirus in hepatocellular carcinoma cells (27), and 5BrdU has been used in human glioma cell combination treatments with 1-nitrosourea and cisplatin (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It can also be noted that PNPase is necessary for bacterial virulence in some well-known pathogens, including the Salmonellae and the Yersiniae (Clements et al 2002;Rosenzweig et al 2007;Numata et al 2014). In addition, it has been proposed that the pool of nucleoside diphosphates generated by PNPase-mediated degradation of RNA plays an important role in the appearance of spontaneous mutations in E. coli (Becket et al 2012).…”
Section: Introductionmentioning
confidence: 99%